2016
DOI: 10.1038/srep19628
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced energy transport owing to nonlinear interface interaction

Abstract: It is generally expected that the interface coupling leads to the suppression of thermal transport through coupled nanostructures due to the additional interface phonon-phonon scattering. However, recent experiments demonstrated that the interface van der Waals interactions can significantly enhance the thermal transfer of bonding boron nanoribbons compared to a single freestanding nanoribbon. To obtain a more in-depth understanding on the important role of the nonlinear interface coupling in the heat transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Most of the studies performed on van der Waals heterostructures to date have been directed towards the measurement of the electron transport through the heterostructure or of the charge transfer at an interface 5 . However, the phonon transport through an interface plays an equally important role 6 7 as it defines the cooling rate and so governs the thermal properties of a multi-layer structure. Specifically, the balance of electron and phonon transport between nanolayers quantifies the efficiency, ZT , in thermoelectric devices 8 9 10 .…”
mentioning
confidence: 99%
“…Most of the studies performed on van der Waals heterostructures to date have been directed towards the measurement of the electron transport through the heterostructure or of the charge transfer at an interface 5 . However, the phonon transport through an interface plays an equally important role 6 7 as it defines the cooling rate and so governs the thermal properties of a multi-layer structure. Specifically, the balance of electron and phonon transport between nanolayers quantifies the efficiency, ZT , in thermoelectric devices 8 9 10 .…”
mentioning
confidence: 99%
“…Particularly, as characteristic lengths of materials approach the energy carriers mean free paths, the transport processes are no longer dominated by scattering inside the bulk materials, but are dominated instead by scattering at heterojunction interfaces. Recently, there have been extensive studies on interfacial thermal conduction through systems of atomic structures via analytical calculations [6][7][8][9][10] and non-equilibrium molecular dynamics (NEMD) simulations [11][12][13]. Meanwhile, experimental studies have shown that interfacial structures and bonding can have a marked effect on thermal transport [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Finally, the method can be exploited to guide the deconvolution of vibrational spectra and to study the phonon-phonon coupling in a broad variety of applications. [33][34][35][36][37]…”
Section: Discussionmentioning
confidence: 99%